PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 26 BENGKALIS - Ernawati, Ernawati; Syahrilfuddin, Syahrilfuddin; Lazim. N, Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low learning outcomes IPA third grade students of SD Negeri 26 Bengkalis. Among the students totaling 28 people, only 12 people (42.86%), which reached the KKM, while 16 (57.14%) who have not reached the KKM, with an average value of 67.00. The activities of teachers in the first cycle of my meetings percentage of 57.14% gain enough categories, at the second meeting of the first cycle increased with the percentage of 64.28% both categories., the first meeting of the second cycle of the teacher's activities also increase the percentage 78.57% into either category and at the second meeting of the second cycle increased again with a percentage of 92.85% is very good category. Student activities at meeting of the first cycle of obtaining a sufficient percentage of the category of 53.57%, in the second meeting of the first cycle increased percentage of 64.28% to the good category, at the first meeting of the second cycle increased with the percentage of 75.00% both categories. At the second meeting of the second cycle increased with the percentage of 92.85% is very good category. From an average of 62.5 study results before action rose to 68.57 in cycle I. In the second cycle increased 73.21. While classical completeness in the first cycle and the second cycle has been reached. can improve learning outcomes IPA third grade students of SD Negeri 26 Bengkalis.Keywords: Model Contextual Teaching And Learning(CTL), Learning Outcomes IPA